2009
DOI: 10.1111/j.1574-6968.2009.01551.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with SsEno fails to protect mice against challenge withStreptococcus suisserotype 2

Abstract: In our ongoing efforts to develop a vaccine against Streptococcus suis infection, we tested the potential of S. suis enolase (SsEno), a recently described S. suis adhesin with fibronectin-binding activity, as a vaccine candidate in a mouse model of S. suis-induced septicemia and meningitis. Here, we show that SsEno is highly recognized by sera from convalescent pigs and is highly immunogenic in mice. Subcutaneous immunization of mice with SsEno elicited strong immunoglobulin G (IgG) antibody responses. All fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…Among them, eight enzymes are proposed to be virulence factors by Wilson et al 100 using the system of signature-tagged mutagenesis (Table 2). Four of them are generally regarded as enzymes of central metabolism, which separately correspond to (1) GlnA, glutamine synthetase, 127 (2) Gdh, glutamate dehydrogenase, 128 (3) enolase catalyzing dehydration of 2-phosphoglycerate to phosphor-enolpyruvate, 96 , 129 , 130 and (4) Impdh, inosine 5-monophosphate dehydrogenase 131 . Five of these enzymes are directly or indirectly related to synthesis and/or modification of bacterial surface structure, including DltA, an enzyme catalyzing lipoteichoic d -alanylation, 132 PgdA, peptidoglycan N-acetylglucosamine deacetylase, 133 ApuA, a bifunctional amylopullulanase, 134 DPP IV, di-peptidyl peptidase IV, 135 and sortase A, a transpeptidase 136 , 137 .…”
Section: Molecular Mechanism For Streptococcus Suis Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, eight enzymes are proposed to be virulence factors by Wilson et al 100 using the system of signature-tagged mutagenesis (Table 2). Four of them are generally regarded as enzymes of central metabolism, which separately correspond to (1) GlnA, glutamine synthetase, 127 (2) Gdh, glutamate dehydrogenase, 128 (3) enolase catalyzing dehydration of 2-phosphoglycerate to phosphor-enolpyruvate, 96 , 129 , 130 and (4) Impdh, inosine 5-monophosphate dehydrogenase 131 . Five of these enzymes are directly or indirectly related to synthesis and/or modification of bacterial surface structure, including DltA, an enzyme catalyzing lipoteichoic d -alanylation, 132 PgdA, peptidoglycan N-acetylglucosamine deacetylase, 133 ApuA, a bifunctional amylopullulanase, 134 DPP IV, di-peptidyl peptidase IV, 135 and sortase A, a transpeptidase 136 , 137 .…”
Section: Molecular Mechanism For Streptococcus Suis Infectionmentioning
confidence: 99%
“…We and two other research groups 96 , 129 , 143 have reported that S. suis enolase acts as an octamer, 144 and can exported to the bacterial surface with capability of binding to host fibronectin, indicating its possible role in crosstalk between pathogen and host. However, the protective efficiency of recombinant enolase with different bacterial origins does not seem consistent 96 , 129 , 130 . Similarly, the gene encoding Inosine 5-monophosphate dehydrogenase, a nucleotide metabolism-related enzyme, was initially cloned by Lu’s research group, and was subsequently suggested to be involved in full virulence of SS2-H, a Chinese strain in the infection model of piglets 131 …”
Section: Molecular Mechanism For Streptococcus Suis Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, enolase is a highly conserved protein, and anti-enolase antibodies have been detected in convalescent pig sera [11]. Nevertheless, immunization studies showed that protection conferred by enolase seems to depend on the adjuvant used in the vaccine formulation [12,13,14]. Similarly, it was recently reported that generation of protective antibodies after immunization with S. suis CPS as antigen was restricted to CPS conjugation to an immunogenic carrier protein and the use of emulsifying adjuvants [15].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, S. suis protein candidates may behave as protective [14,22] or non-protective [12,28] immunogens at least in part depending on the adjuvant. Compared to human medicine, a wider range of adjuvants has been successfully used in commercial vaccines for animals and several new technologies are currently in preclinical development (reviewed in [29,30]).…”
Section: Introductionmentioning
confidence: 99%